Peran Corporate Social Responsibility (CSR) dalam Pemberdayaan Ekonomi Nelayan: Studi Literatur pada Program Pemberdayaan Pesisir di Tanjungpinang - Dhea Octavia; Palentin Enjelika Turnip; Paulina Heppy Fridayanti Waruwu (Universitas 17 Agustus 1945, 2025)
This research examines the role of Corporate Social Responsibility (CSR) in supporting the economic empowerment of fishing communities in Tanjungpinang. The study is motivated by the persistence of economic vulnerability among fishermen despite the availability of marine resources and ongoing CSR initiatives. Using a qualitative approach with library research methods, this study analyzes academic literature, government documents, and CSR program reports to understand how CSR has been implemented and its implications for community empowerment. The findings show that CSR programs in coastal areas generally remain charitable in nature, focusing on the provision of temporary assistance rather than strengthening the capacity and autonomy of fishermen. As a result, the programs have not significantly contributed to sustainable economic resilience. This study argues that CSR needs to be reoriented toward participatory empowerment, capacity building, and alignment with sustainable development and blue economy principles to support long-term welfare. The study also suggests the importance of further empirical research to validate implementation outcomes.